Correction: Calculation of the Average Cost per Case of Dengue Fever in Mexico Using a Micro-Costing Approach. - Adriana Zubieta-Zavala; Guillermo Salinas-Escudero; Adrian Ramírez-Chávez; Luis García-Valladares; Malaquias López-Cervantes; Juan Guillermo López Yescas; Luis Durán-Arenas (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004897.].